Neural correlates of basketball proficiency: An MRI study across skill levels - Manqi Zhang; Wenbiao Zhang; Yujie Yao; Jiabao Lin; Lei Mo (Journal of Exercise Science & Fitness)
Background: Basketball is an attractive sport required both cooperative and antagonistic motor skills. However, the neural mechanism of basketball proficiency remains unclear. This study aimed to examine the brain functional and structural substrates underlying varying levels of basketball capacity. Methods: Twenty advanced basketball athletes (AB), 20 intermediate basketball athletes (IB) and 20 age-matched non-athlete individuals without basketball experience (NI) participated in this study and underwent T1-weighted MRI and resting-state fMRI scanning. Voxel-mirrored homotopic connectivity (VMHC), amplitude of low frequency fluctuations (ALFF), and gray matter (GM) density were calculated and compared among the three groups. Results: The VMHC in the bilateral postcentral gyrus, middle temporal gyrus, and superior temporal gyrus, as well as the GM density in the right precentral gyrus, exhibited a hierarchical structure of AB > IB > NI. Compared with NI group, AB and IB groups showed strengthened VMHC in supplementary motor area, paracentral lobule and superior frontal gyrus. Additionally, the ALFF of left middle occipital gyrus and right hippocampal and the GM density of left medial superior frontal gyrus exhibited differences in AB-IB and AB-NI comparisons. Conclusions: By conducting the cross-sectional comparison, this study firstly identifies the varying levels of basketball proficiency related brain resting-state functional and structural plasticity. Especially, the regions associated with motor perception and control, including bilateral postcentral gyrus, middle and superior temporal gyrus and right precentral gyrus, are involved in the key neural mechanisms of basketball proficiency. Future longitudinal studies are necessary to further validate these findings.